2009
DOI: 10.1002/adem.200800298
|View full text |Cite
|
Sign up to set email alerts
|

New Materials in Memory Development Sub 50 nm: Trends in Flash and DRAM

Abstract: New materials are of key importance for scaling memories in the sub 50 nm generations. Currently high‐k materials and metal gates are investigated for usage in Flash and DRAM memory. However, the requirements in the applications are different, leading to different material combinations. This paper gives an overview on new materials with focus on memory applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Moreover, studies on atomic layer deposition of Ru from advanced precursors such as (methylcyclopentadienyl)(pyrrolyl)ruthenium on SrTiO 3 [15] have revealed that the growth of Ru on such materials is poorly controlled unless plasma-assisted cleaning of underlying oxide film is applied despite the possible structural damage of the oxide surface. Nevertheless, noble metal electrodes (Ru, RuO 2 ) are of significant importance [16,17] despite the related increase in processing costs. Notable amount of studies on Ru so far have been devoted to the issues related to the nucleation of ruthenium thin films as well as to the parametrization of growth processdependence of the growth rate and roughness on growth temperature, pressure and time [2,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on atomic layer deposition of Ru from advanced precursors such as (methylcyclopentadienyl)(pyrrolyl)ruthenium on SrTiO 3 [15] have revealed that the growth of Ru on such materials is poorly controlled unless plasma-assisted cleaning of underlying oxide film is applied despite the possible structural damage of the oxide surface. Nevertheless, noble metal electrodes (Ru, RuO 2 ) are of significant importance [16,17] despite the related increase in processing costs. Notable amount of studies on Ru so far have been devoted to the issues related to the nucleation of ruthenium thin films as well as to the parametrization of growth processdependence of the growth rate and roughness on growth temperature, pressure and time [2,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the capacitance equivalent thickness (CET) requirement in DRAMs for the oxide fi lm is below 1 nm and will decrease to 0.5 nm in the near future, while keeping the leakage current density below 10 -7 A/cm 2 at 1 V. 4 At the moment, the most widely used dielectric material in DRAMs is an ALD-formed ZrO 2 -Al 2 O 3 -ZrO 2 nanolaminate. 5 The transition of ALD high-κ oxides to the product level required extensive research and development, including the analysis of a wide range of precursor materials and processes. Most of the attention has been devoted to hafnium and zirconium oxides, but rare-earth metal oxides and other doping systems have also been studied.…”
Section: High-κ Oxidesmentioning
confidence: 99%
“…[11] However, in a few years with a design rule of <40 nm, the CET must be lowered to <0.5 nm while keeping the leakage current density below 10 À7 A cm À2 at 1 V in the metal-insulator-metal (MIM) structures. [4] The selection of high-k materials for these requirements is challenging.…”
Section: High-k Dielectrics For Memory Applicationsmentioning
confidence: 99%
“…More detailed discussion on current trends in new materials for memory development, including flash technology and logic devices in DRAM technology, is given in another article in this special issue. [11] 4. ALD of Binary and Ternary High-k Dielectrics Oxides of Group 4 metals…”
Section: High-k Dielectrics For Memory Applicationsmentioning
confidence: 99%
See 1 more Smart Citation